Roll‐to‐Roll Hot Embossing of 1D and 2D Photonic Nanostructures. Issue 8 (20th May 2019) - Habermehl, Anne; Brenner, Philipp; Huber, Robert; Mertens, Adrian; Winkler, Frank; Hahn, Lothar; Guttmann, Markus; Eschenbaum, Carsten; Lemmer, Uli
Abstract : Roll‐to‐roll hot embossing is exploited for the fabrication of 1D nanogratings and 2D nanopillar arrays. Critical structure diameters as low as 150 nm and distances down to 50 nm are replicated in a polystyrene foil using flexible nickel shims, which are made using electron beam lithography and subsequent electroplating. The high quality of the as‐fabricated structures is proven by their application in two key nanophotonic components. After evaporation of 250 nm of Alq3:DCM on 1D nanogratings using grating periods between 375 and 415 nm, we can realize tunable organic DFB lasers emitting between 604 and 665 nm. 2D nanopillar arrays are covered with a thermally evaporated Au layer and integrated in microfluidic chips for surface‐enhanced Raman measurements. High and homogeneous enhancement of the Raman signal is achieved using rhodamine 6G as exemplary analyte. For polystyrene nanopillar arrays with pillar diameters of 190 nm, a spacing of 50 nm, and a height of 100 mm coated with a 70 nm thick Au layer, an analytical enhancement factor of ≈4.3 × 10 4 is demonstrated. The presented work shows the versatility of roll‐to‐roll hot embossing for the low‐cost and large‐area fabrication of nanostructures. Abstract : Roll‐to‐roll hot embossing is exploited for the fabrication of 1D nanogratings and 2D nanopillar arrays with critical structure diameters as low as 150 nm and distances down to 50 nm in a polystyrene foil. The high quality of the as‐fabricated structures is proven by their application in two key nanophotonic components, namely tunable organic DFB lasers and as SERS substrates with high and homogeneous enhancement.